The Mouse Secretome: Functional Classification of the Proteins Secreted Into the Extracellular Environment - Grimmond, Sean M.; Miranda, Kevin C.; Yuan, Zheng; Davis, Melissa J.; Hume, David A.; Yagi, Ken; Tominaga, Naoko; Bono, Hidemasa; Hayashizaki, Yoshihide; Okazaki, Yasushi; RIKEN GER Group; GSL Members; et al. (Genome Research, 2003)
We have developed a computational strategy to identify the set of soluble proteins secreted into the extracellular environment of a cell. Within the protein sequences predominantly derived from the RIKEN representative transcript and protein set, we identified 2033 unique soluble proteins that are potentially secreted from the cell. These proteins contain a signal peptide required for entry into the secretory pathway and lack any transmembrane domains or intracellular localization signals. This class of proteins, which we have termed the mouse secretome, included >500 novel proteins and 92 proteins <100 amino acids in length. Functional analysis of the secretome included identification of human orthologs, functional units based on InterPro and SCOP Superfamily predictions, and expression of the proteins within the RIKEN READ microarray database. To highlight the utility of this information, we discuss the CUB domain-containing protein family.